Pediatric rheumatology in Africa: thriving amidst challenges - Angela N. Migowa; Djohra Hadef; Wafa Hamdi; Oscar Mwizerwa; Madeleine Ngandeu; Yassmin Taha; Faleye Ayodele; Kate Webb; Christiaan Scott (BMC, 2021)
Abstract Background Pediatric Rheumatology is an orphan specialty in Africa which is gradually gaining importance across the continent. Main body This commentary discusses the current state of affairs in the sphere of Pediatric Rheumatology across Africa and offers practical strategies to navigate the challenges encountered in research, models of care, education and training. We outline the establishment, opportunities of growth and achievements of the Pediatric Society of the African League Against Rheumatism (PAFLAR). Conclusion This commentary lays the foundation for establishment of a formidable framework and development of partnerships for the prosperity of Pediatric Rheumatology in Africa and beyond.